Analisis Keberlanjutan Usaha Peternakan Ayam Broiler yang Bermitra pada PT Indojaya Agrinusa di Kecamatan Tapung Kabupaten Kampar - Sandra, Mentari Dewi; Cepriadi, Cepriadi; Herlon, Meki (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Tapung Subdistrict is one of the subdistricts with the largest broiler population and the largest number of partnered broiler farmers in Kampar Regency. With the increasing market demand for broiler chickens, business opportunities in broiler farming are automatically getting better. The main problems of broiler farming are related to large capital, fluctuations in the prices of farm inputs and outputs, and risks during cultivation. This condition makes farmers have to cooperate with companies to ensure the sustainability of their broiler farming business. This study aims to analyze the level of sustainability of broiler farming and find out what sensitive attributes affect the sustainability of broiler farming in partnership patterns. The research method used is a survey method with a sample size of 5 respondents taken using the purposive sampling method. Data analysis was conducted using Multidimensional Scaling (MDS) through the RAPFISH approach and leverage analysis to determine the most influential attributes. The results showed that overall the broiler farming business partnering with PT Indojaya Agrinusa in Tapung District, Kampar Regency, has a fairly sustainable status. The results of the leverage analysis show that there are 16 sensitive attributes that can affect the sustainability of the 32 attributes used.